Na rota dos festivais: uma tradição que se renova - Andréa Betânia da Silva (Estudos de Literatura Brasileira Contemporânea)
Orality is an advantageous space to the development of research and thinking that aims at altering, or at least re-thinking, theoretical bases that seem quite strong. In this aim, the present article looks at a trajectory established in Northeast Brazil’s improvised singing, more specifically the universe of poetic match, coming from the “pés de parede” (simple matches) to the festivals of guitar players that spread themselves through Northeast Brazil, aiming to realize that cultural contexts gave birth, if not to invention, at least the renewal of a tradition.